American Cancer Society lung cancer screening guidelines1. (11th January 2013) - Wender, Richard; Fontham, Elizabeth T. H.; Barrera, Ermilo; Colditz, Graham A.; Church, Timothy R.; Ettinger, David S.; Etzioni, Ruth; Flowers, Christopher R.; Scott Gazelle, G.; Kelsey, Douglas K.; LaMonte, Samuel J.; Michaelson, James S.; et al.
Abstract Answer questions and earn CME/CNE Findings from the National Cancer Institute's National Lung Screening Trial established that lung cancer mortality in specific high‐risk groups can be reduced by annual screening with low‐dose computed tomography. These findings indicate that the adoption of lung cancer screening could save many lives. Based on the results of the National Lung Screening Trial, the American Cancer Society is issuing an initial guideline for lung cancer screening. This guideline recommends that clinicians with access to high‐volume, high‐quality lung cancer screening and treatment centers should initiate a discussion about screening with apparently healthy patients aged 55 years to 74 years who have at least a 30–pack‐year smoking history and who currently smoke or have quit within the past 15 years. A process of informed and shared decision‐making with a clinician related to the potential benefits, limitations, and harms associated with screening for lung cancer with low‐dose computed tomography should occur before any decision is made to initiate lung cancer screening. Smoking cessation counseling remains a high priority for clinical attention in discussions with current smokers, who should be informed of their continuing risk of lung cancer. Screening should not be viewed as an alternative to smoking cessation. CA Cancer J Clin 2013;. © 2013 American Cancer Society.